Prophet Muhammad: The Night Journey The Night Journey - Khan, Saniyasnain (Ajman,U.A.E Iqra book Distribution, 2024)
This enchantingly illustrated board book, delightfully introduces to the children the inspiring life and teachings of the Prophet Muhammad
Keywords: islamic book